Selbsterziehung in China - Guoqin, Shen [Verfasser] (My University, 2011)
"The transitions of social structures and educational outlines are introduced. The author shows that self-education has played a significant role not only in the progress of the development of individuals in China but also in the process of socialization. Nowadays, self-education is considered in the framework of interaction with others' education. Several methods adopted for self-education in China are listed. The author analyses why psychological system of self-education is actually te self-consciousness of a certain individual in China. The author points out a few essential characteristics of self-education in China describes several specific approaches of nurturing the abilities of self-education, and gives an outlook on the future development of self-education in China." (Autorenreferat, BIBB-Doku)
Keywords: I 2.3.4 Asien; G 2.4 Sozialer Wandel; G 2.4.2 Lebenskonzepte, -stile, Werte; T 4.9 Pädagogik; Sozialer Wandel; Bildungspolitik; Bildungsreform; Erziehungsziel; Selbstgesteuertes Lernen; Selbstverwirklichung; Wertewandel; Sozialisation; China